THE NEED AND PURPOSE OF THE RAILWAY TRANSPORT REFORMATION IN UKRAINE - Snitko, M. P.; Sokolovska, M. S.; Radionov, I. P. (Science and Transport Progress, 2007)
The critical obsolescence of basic facilities in all economies of railways of Ukraine physical and, and cross subsidizing of passenger transportations due to freight, «investment hunger» absence of state support of industry, caused the necessity of reformation of rail-way transport of Ukraine. In the article authors consider ways and mechanisms of government control of the folded position in industry.